Peran Lembaga Pengelola Investasi dalam Menunjang Investasi Nasional - Mahdaniah Mahdaniah (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2025)
Investment Management Institution (LPI) as an entity, LPI is an institution established by law and is responsible to the President so that it has high credibility and perception of stability internationally. LPI's assets are also included in the Separated State Assets. As a sui generis institution, LPI has strong independence and professional management, this aims to maximize investors who want to invest in Indonesia. Institutionally, LPI has elements as a public legal subject because LPI in its operations uses a budget sourced from state finances. In addition, LPI also has characteristics as a private legal subject in terms of carrying out investment activities or capital investment.